"Chronic myelogenous leukemia in primary blast crisis" rather than "de novo BCR‐ABL1‐positive acute myeloid leukemia". Issue 6 (4th April 2017) - Pastoret, Cedric; Houot, Roch
Key Clinical Message: Differentiating chronic myelogenous leukemia in primary blast crisis (CML‐BC) from de novo BCR‐ABL1 ‐positive acute myeloid leukemia (AML) is a diagnostic challenge with therapeutic consequences. In our case, a basophilia, the presence of the Philadelphia chromosome in all metaphases and the strict exclusion of molecular hallmarks of AML lead us to retain the diagnosis of CML‐BC rather than BCR‐ABL1+ AML. Abstract : Differentiating chronic myelogenous leukemia in primary blast crisis (CML‐BC) from de novo BCR‐ABL1 ‐positive acute myeloid leukemia (AML) is a diagnostic challenge with therapeutic consequences. In our case, a basophilia, the presence of the Philadelphia chromosome in all metaphases and the strict exclusion of molecular hallmarks of AML lead us to retain the diagnosis of CML‐BC rather than BCR‐ABL1+ AML.